Une promise pour la licorne : quand Denis Johnston crève l’horizon de la scène irlandaise - Virginie Girel-Pietka (Revue LISA)
Unlike his first two plays, Denis Johnston’s A Bride for the Unicorn, produced in 1933 at the Gate Theatre in Dublin, was not a success. It did not meet the audience’s or the critics’ expectations since the playwright aimed at redefining them. He endeavoured to create an original piece of work, breaking away from the realistic drama which prevailed in Ireland at the time. Fraught with mythological references and hazy characters, the play was considered too complicated, even obscure, and vaguely moralistic. Examining the way Johnston turned his back on the Aristotelian tradition so as to usher Modernism onto the stage, this paper aims at showing that the play was rather meant to open up new aesthetic prospects for the Irish drama of its time. In the wake of World War I and the worldwide Great Depression, mimesis was out of fashion. The play therefore focused on the individual’s never-ending quest for identity, thus offering food for thought as regards the art of theatre.